Penyusunan Laporan Keuangan Pada Sumurboto Stationery Semarang Tahun 2016 Berdasarkan Sak Etap - Lasa Laksita; Adilistiono Adilistiono (Politeknik Negeri Semarang, 2018)
Financial statement preparation is very important because it can describe the finance of an entity and as a basis for decision making. The purpose of this Final Project is to prepare the company's financial statements consisting of Balance Sheet, Income Statement, Statement of Changes in Equity and Cash Flow Statement based on Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP), with the result that assist Sumurboto Stationery in preparing financial statements. Interview and documentation are used in data collection method. On the other hand, this Final Project used description and exposition method for the writing method. The result of this Final Project is to gain the knowledge in how have Sumurboto Stationery done their financial statement preparation in 2016 based on Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP) that consisting of Income Statement, Statement of Changes in Equity, Balance Sheet and Cash Flow Statement. Hopefully, Sumurboto Stationery can be able to prepare their financial statement for the next period in accordance with Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP)